“The Dream Machine”: Entrepreneurial Education Program for Primary and Middle School Students - Vega, María Paula (Ingeniería Solidaria, 2015)
This article is a case report on the program entitled “Innovation and Enterprise” (“Innova y Emprende”), a permanent extension project at the Engineering Faculty of the Universidad Fasta. In this program, a series of workshops was held with the education community. One such workshop was called “Little Big Dreamers” (“Pequeños Grandes Soñadores”) and was held in Mar del Plata, Argentina, from March to September 2014. The objective was to empower fifth and sixth grade secondary students at Basic Middle School N° 45 to encourage them to dream and plan their futures. Technology was employed as the facilitating medium for realizing their dreams. The students learned to design their own presentations using Scratch (a programming language for children and adolescents) to develop computational thinking and creativity; they created characters according to their own personal image and incorporated rap music with rhythm and lyrics to express their way of seeing the world. The results obtained through this project helped to awaken the curiosity of the participating adolescents, to develop the necessary abilities for enterprise and find the needed enthusiasm to successfully finish the project.